Underwater Channel Characterization to Design Wireless Sensor Network by Bellhop - Nima Bahrami; Nor Hisham Haji Khamis; Ameruddin Baharom; Azli Yahya (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Acoustic underwater link due to low attenuation is employed for underwater sensor network (UWSN). Due to water changing physical properties and different environmental conditions, the sound propagation for every underwater channel are different. So, the most important parameters to design reliable UWSN are: the shadow zone determination, optimum nodes placement, high signal to noise ratio and more power efficiency of nodes. This paper simulates underwater channel for 7 KHz carrier frequency, with measured physical water properties and remote sensing data. Based on defined scenario, the research determines optimum nodes placement and link budget analysis based on bottom to surface acoustic link. The paper utilizes Bellhop acoustic toolbox as a simulator, GeoMapApp program to collects bathymetry data and Aviso+ database to determine wind speed on sea surface. As a result the paper based on simulation of sound propagation in channel and transmission loss determination in depth and range, finds the optimum nodes positions and link budget calculation to prove the results.